Preterm‐born children's development: A bioecological perspective. Issue 1 (14th November 2022) - Barra, Lisseth; Coo, Soledad
Abstract: Preterm birth is a biological risk factor for developmental problems. Infants born preterm are more likely to present difficulties and potential delays in all areas of development. The aim of the present review is to apply Bronfenbrenner´s bioecological model of human development to understand the factors that shape the developmental trajectories of infants born preterm. This model offers a developmental science perspective, which considers the dynamic interaction of diverse processes and contextual factors across the lifespan to explain developmental trajectories. Firstly, the article provides key definitions associated with preterm birth and the relevance of this condition from a public health perspective. Secondly, we describe why preterm birth is a neurobiological risk factor for optimal development. Then, we describe the components of the bioecological model, provide examples associated with infants born preterm, and describe available evidence on how psychosocial factors influence development in this population. This review contributes to a deeper understanding of the factors that influence the development of infants born preterm from an integrative and complex perspective and discuss some implications of using this approach for clinical practices oriented to infants born preterm. Highlights: Preterm birth is a relevant public health problem. Child development in preterm‐born infants has been studied mainly from a biomedical perspective. Prematurity is analysed from a developmental science perspective, specifically from the bioecological model. Growing up in adverse psychosocial contexts may negatively impact premature children. Developmental sciences may contribute to clinical practices and research related to preterm infants.